RESPON PEMBERIAN PUPUK PHONSKA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays Saccharata Sturt) - Fiolent Dolsenyawi; Fransin Polnaya; Imelda J. Lawalata (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
This study was conducted to analyze the impact of Phonska fertilizer application on the vegetative development and yield of sweet corn (Zea mays Saccharata Sturt.). The research activities were carried out in Waesamu Village, West Seram Regency during the period from May to July, employing a Randomized Block Design (RBD) with various dosage levels of Phonska fertilizer as treatment factors. Observation parameters included plant height measurements, leaf quantity, stem diameter measurements, leaf surface area, weight of husked ears, weight of dehusked ears, ear length measurements, ear diameter measurements, number of rows per ear, number of kernels per ear, and harvest index. Data analysis was performed through analysis of variance (ANOVA) followed by Honestly Significant Difference (HSD) test at 5% significance level. Research findings indicated that Phonska fertilizer application had a significant impact on both the vegetative growth phase and production output of sweet corn. The optimal Phonska fertilizer dosage [400 kg/ha] yielded the best performance across all growth and production parameters, demonstrated by increased ear mass and higher yield per hectare compared to other treatments. In conclusion, the application of Phonska fertilizer at the appropriate dosage proved effective in enhancing sweet corn productivity and can be recommended for cultivation practices of this crop.